Determination of Breast Cancer Risk at Dr. Wahidin Sudirohusodo Hospital - Sulfikar, Andi; Restika, Indah (Innovative Approaches in Health Science Journal, 2024)
Breast cancer is one of the most common types of cancer among women and represents a significant cause of mortality. This study aims to identify the determinants of breast cancer risk among patients treated at RSUP Dr. Wahidin Sudirohusodo Makassar. The study employed a cross-sectional design with a sample of 81 respondents selected through purposive sampling. Data were collected through interviews and questionnaires and analyzed using chi-square tests and logistic regression to identify the relationships between risk determinants and the occurrence of breast cancer. The findings of this study are expected to provide insights into the risk factors contributing to breast cancer and support the development of more effective prevention strategies.